TAXATION KNOWLEDGE, MOTIVATION TO PAY TAX AND EDUCATION LEVEL ON PERSONAL TAXPAYER OBLIGATION COMPLIANCE - Saifudin Saifudin; Aprih Santoso; Meitri Yana Wardani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to find out: (1) The effect of taxation knowledge, (2) motivation to pay tax, and (3) education level on personal taxpayer compliance at KPP Pratama of East Semarang. The samples in this research are 120 personal taxpayers. The sample collection technique used in this research is Incidental Sampling. The data collection method uses questionnaire. The method of analysis used in this research was statistical descriptive analysis, data quality test, classical assumption test and hypothesis test. Data were analyzed by multiple regression analysis using SPSS Version 23. The results of this study state that taxation knowledge, motivation to pay tax, and education level have positive impact on taxpayer compliance. Keywords: Taxation knowledge, Motivation to Pay Tax, Education Level, Taxpayer Compliance.